Evaluation of spray-dried cheese food as a supplemental protein source for weanling pigs - J A Loughmiller; P S Graf; J R Bergstrom; R E Muser; Jim L Nelssen; Robert D Goodband; Michael D Tokach; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 1996)
A growth study was conducted to determine the effects of substituting spray-dried cheese food for spray-dried plasma protein on weanling pig performance. Five dietary treatments included the control diet or diets with cheese food replacing 25, 50, 75, and 100% of the plasma on an equal lysine basis. Day 0 to 14 ADG and ADFI were decreased linearly as spray-dried cheese food increased. However, this decrease was most apparent when cheese food was included at more than 4% of the diet. No effects of cheese food inclusion were seen for F/G from d 0 to 14 postweaning or for growth performance from d 14 to 28 or from d 0 to 28 postweaning. These results indicate that spray-dried cheese food resulted in a linear reduction in ADG and ADFI. However, the growth reduction was not apparent until cheese food was included at more than 4% of the diet.; Swine Day, Manhattan, KS, November 21, 1996
Keywords: Swine day; 1996; Kansas Agricultural Experiment Station contribution; no. 97-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 772; Swine; Cheese food; Protein; Nursery pigs